2015
DOI: 10.11607/prd.2116
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Regeneration Technology to Solve Peri-implantitis by Er:YAG Laser Based on the Microbiologic Diagnosis: A Case Series

Abstract: is an emerging problem, and corrective therapy requires a method for decontaminating the complex surface structure of the implant body and sterilizing the surrounding tissue. The erbium:yttrium-aluminum-garnet (Er:YAG) laser has proven to effectively allow tissue to regenerate when used for peri-implantitis. The power of the Er:YAG laser is absorbed by a water molecule; therefore, its target neither rises in temperature nor carbonizes. An antibacterial remedy based on the bacteriologic diagnosis, followed by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
(18 reference statements)
0
16
0
Order By: Relevance
“…Seven articles reporting four randomized controlled trials [14,30,32,33] and three prospective case series [31,34,76] were included in this review (Table 4). Two studies evaluated the photothermal effect of the diode laser [30,77], two evaluated the Er:YAG laser [32,34] and three evaluated aPDT (antimicrobial photodynamic therapy) [14,31,76] on peri-implant pathogens. Various bacterial profiles were assessed in the articles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven articles reporting four randomized controlled trials [14,30,32,33] and three prospective case series [31,34,76] were included in this review (Table 4). Two studies evaluated the photothermal effect of the diode laser [30,77], two evaluated the Er:YAG laser [32,34] and three evaluated aPDT (antimicrobial photodynamic therapy) [14,31,76] on peri-implant pathogens. Various bacterial profiles were assessed in the articles.…”
Section: Resultsmentioning
confidence: 99%
“…Yoshino et al [34], in their study on the Er:YAG laser, reported eradication of oral pathogens. Additionally, Persson et al [32] showed lower bacterial counts in the laser-treated group for F. nucleatum naviforme and F. nucleatum nucleatum at 1 month after treatment and in comparison to baseline levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiographically, PDs were reduced due to peri-implant defect bone fill. Similarly, Yoshino et al 66 found that antibiotic therapy significantly reduced the bacterial amount from the peri-implantitis sites and that Er:YAG laser therapy, along with bone augmentation, enhanced bone regeneration in the peri-implant bone defects.…”
Section: Simulated Radiation Emission (Lasers)mentioning
confidence: 90%
“…reported that a combination of Er,Cr:YSGG laser and conventional scaling and root plaining had better results compared to scaling root-plaining alone in terms of attachment level restoration. Other types of high intensity lasers such as Er:YAG and Nd:YAG lasers have been recently used in a way similar to Er,Cr:YSGG in the periodontal therapy [ 22 , 23 ]. Er:YAG lasers are securely used as an alternative to non-surgical periodontal therapy or as an adjunct for pocket treatment [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%